THE RELATIONSHIP BETWEEN AROUSAL ZONE, ANXIETY, STRESS AND SPORTS PERFORMANCE - Németh, Kata; Balogh, László (Stadium - Hungarian Journal of Sport Sciences, 2020)
This study aimed to examine the relationship between optimal functioning zone, anxiety, stress, and athletic performance. We conducted a systematic review of the available scientific articles and publications. Related literature was analyzed, relevant, or helpful in understanding the psychological aspects of athletic performance. It discusses the method and validity of hypotheses and approaches that have already appeared scientifically. We examined multidimensional approaches, which discuss the suitability and implications of some recent and more complex models of stress and performance. We may conclude that the relationship between stress and athletic performance is multidimensional. We also examined several factors, such as the interaction between the nature of the stressor, the cognitive needs of the task, and the individuals' psychological characteristics. Both physical and mental preparation is critical to successful sports performance. This way, the level of physical skills, mental preparedness significantly determine overall athletic performance. The article aims to provide a historical overview of the implementation, testing, and measurement of IZOF and other applied models.